2006
DOI: 10.1159/000103385
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Neural Stem Cells Expanded in Lowered Oxygen and the Potential Role of Hypoxia-Inducible Factor-1Alpha

Abstract: It has recently been reported that hypoxia promotes the survival and proliferation of neural stem cells (NSCs). In the present study, we examine the differentiation ability of neural precursors expanded under lowered oxygen conditions, and the potential role of hypoxia-inducible factor (HIF)-1αin vitro, which is the key molecule in response to lowered oxygen. The NSCs were cultured in a 3% O2 environment for 3 days, and differentiated with 1% fetal bovine serum (FBS) for another 5–7 days, and the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 20 publications
5
39
0
Order By: Relevance
“…Cells derived from Wistar rat mesencephalon (E13.5) were mechanically dissociated, and grown in DMEM/F12 (1:1) medium containing 2 mM L-glutamine, 5 IU of penicillin, 5 μg/ml streptomycin (BioWhittaker), 1% N2 (Life Technologies), 1% B27 (Life Technologies), 20 ng/ml epidermal growth factor (EGF; Sigma) and 20 ng/ml basic fibroblast growth factor (bFGF; R&D Systems, Minneapolis, MN; Zhang et al 2007). Cells were plated on plastic 35 mm dishes precoated with poly-L-lycine.…”
Section: Isolation and Culture Of Npcsmentioning
confidence: 99%
“…Cells derived from Wistar rat mesencephalon (E13.5) were mechanically dissociated, and grown in DMEM/F12 (1:1) medium containing 2 mM L-glutamine, 5 IU of penicillin, 5 μg/ml streptomycin (BioWhittaker), 1% N2 (Life Technologies), 1% B27 (Life Technologies), 20 ng/ml epidermal growth factor (EGF; Sigma) and 20 ng/ml basic fibroblast growth factor (bFGF; R&D Systems, Minneapolis, MN; Zhang et al 2007). Cells were plated on plastic 35 mm dishes precoated with poly-L-lycine.…”
Section: Isolation and Culture Of Npcsmentioning
confidence: 99%
“…Low atmospheric oxygen levels of 3% confer long-term proliferation and stem cell maintenance of midbrain dopaminergic NPCs in vitro, including the conservation of their dopaminergic differentiation potential, and avoid senescence in various species, including mouse [18][19][20][21][22][23][24]. Further in vitro studies have shown that the oxygen-dependent transcription factor hypoxiainducible factor 1a (HIF-1a) is involved in these processes [15,25,26] and is responsible for the initial adaptive response of cells to oxygen variations [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…It is now known that lowered oxygen concentration enhances neurogenesis and delays certain differentiation processes (15,16). For instance, HIF1␣ interacts with Notch1 to maintain undifferentiated cell states (5), whereas HIF2␣ binds to the marker of the undifferentiated state Oct4 promoter, inducing its expression and transcriptional activity (8).…”
mentioning
confidence: 99%